Distribution of Problems, Medications and Lab Results in Electronic Health Records: The Pareto Principle at Work - Wright, Adam, PhD; Bates, David W., MD, MSc (Applied Clinical Informatics, 2010)
Background: Many natural phenomena demonstrate power-law distributions, where very common items predominate. Problems, medications and lab results represent some of the most important data elements in medicine, but their overall distribution has not been reported.Objective: Our objective is to determine whether problems, medications and lab results demonstrate a power law distribution.Methods: Retrospective review of electronic medical record data for 100,000 randomly selected patients seen at least twice in 2006 and 2007 at the Brigham and Women’s Hospital in Boston and its affiliated medical practices.Results: All three data types exhibited a power law distribution. The 12.5% most frequently used problems account for 80% of all patient problems, the top 11.8% of medications account for 80% of all medication orders and the top 4.5% of lab result types account for all lab results.Conclusion: These three data elements exhibited power law distributions with a small number of common items representing a substantial proportion of all orders and observations, which has implications for electronic health record design.
Keywords: Data Mining; Electronic Health Records; Statistical Distributions